Meditation Increases the Entropy of Brain Oscillatory Activity. (1st April 2020) - Martínez Vivot, Rocío; Pallavicini, Carla; Zamberlan, Federico; Vigo, Daniel; Tagliazucchi, Enzo
Highlights: Vipassana meditation increased the entropy of alpha 1 and gamma oscillation envelopes. Classifiers trained on Vipassana scalp entropy distributions generalized well to other meditation traditions. All meditation traditions increased gamma band coherence. All meditation traditions decreased gamma band metastability. Abstract: We address the hypothesis that the entropy of neural dynamics indexes the intensity and quality of conscious content. Previous work established that serotonergic psychedelics can have a dysregulating effect on brain activity, leading to subjective effects that present a considerable overlap with the phenomenology of certain meditative states. Here we propose that the prolonged practice of meditation results in endogenous increased entropy of brain oscillatory activity. We estimated the entropy of band-specific oscillations during the meditative state of traditions classified as 'focused attention' (Himalayan Yoga), 'open monitoring' (Vipassana), and 'open awareness' (Isha Shoonya Yoga). Among all traditions, Vipassana resulted in the highest entropy increases, predominantly in the alpha and low/high gamma bands. In agreement with previous studies, all meditation traditions increased the global coherence in the gamma band, but also stabilized gamma-range dynamics by lowering the metastability. Finally, machine learning classifiers could successfully generalize between certain pairs of meditation traditions based on the scalp distribution of gamma band entropies. Our results extend previous findings on the spectral changes observed during meditation, showing how long-term practice can lead to the capacity for achieving brain states of high entropy. This constitutes an example of an endogenous, self-induced high entropy state.